Never Again : a History of the Holocaust. - Gilbert, Martin (RosettaBooks, 2015)
A work forty years in the making'Sir Martin Gilbert's illustrated survey of the pre- and post-war history of the Jewish people in Europe. Masterfully covering such topics as pre-war Jewish life, the Warsaw Ghetto revolt, and the reflections of Holocaust survivors, Gilbert interweaves firsthand accounts with unforgettable photographs and documents, coming together to form a three-dimensional portrait of the lives of the Jewish people during one of Europe's darkest times. "This volume introduces the crime to a new generation, so that it knows of the atrocities and the seemingly futile acts of defiance taken, in the words of Judah Tenenbaum, 'for three lines in the history books.'" 'Booklist